In the lives of puppets - Klune, TJ (Tor Publishing Group, 2023)
"New York Times bestselling author TJ Klune invites you deep into the heart of a peculiar forest and on the extraordinary journey of a family assembled from spare parts. In a strange little home built into the branches of a grove of trees, live three robots-fatherly inventor android Giovanni Lawson, a pleasantly sadistic nurse machine, and a small vacuum desperate for love and attention. Victor Lawson, a human, lives there too. They're a family, hidden and safe. The day Vic salvages and repairs an unfamiliar android labelled "HAP," he learns of a shared dark past between Hap and Gio-a past spent hunting humans. When Hap unwittingly alerts robots from Gio's former life to their whereabouts, the family is no longer hidden and safe. Gio is captured and taken back to his old laboratory in the City of Electric Dreams. So together, the rest of Vic's assembled family must journey across an unforgiving and otherworldly country to rescue Gio from decommission, or worse, reprogramming. Along the way to save Gio, amid conflicted feelings of betrayal and affection for Hap, Vic must decide for himself: Can he accept love with strings attached? Inspired by Carlo Collodi's The Adventures of Pinocchio, and like Swiss Family Robinson meets Wall-E, In the Lives of Puppets is a masterful stand-alone fantasy adventure from the beloved author who brought you The House in the Cerulean Sea and Under the Whispering Door"--